New electrochemical methods. - Batchelor-McAuley, C; Dickinson, E; Rees, N; Toghill, K; Compton, R (2012)
This review is predominantly focused upon articles dating from 2009 to 2011. The authors have attempted to highlight areas of recent and significant development, with the aim of providing the reader with a clear and concise view of the current state-of-the-art in areas ranging from fundamental electrochemistry to applied methods for biological analysis. Specific areas of interest include recent developments in surface analysis techniques, single-molecule and nanoparticle stochastic analysis, and nanopore technology